Mitochondrial DNA haplogroups and trajectories of cardiometabolic risk factors during childhood and adolescence: A prospective cohort study. - Kate N O'Neill; Emily Aubrey; Laura D Howe; Evie Stergiakouli; Santiago Rodriguez; Patricia M Kearney; Linda M O'Keeffe (PLoS ONE)
Background Mitochondria are organelles responsible for converting glucose into energy. Mitochondrial DNA is exclusively maternally inherited. The role of mitochondrial DNA haplogroups in the aetiology of cardiometabolic disease risk is not well understood. Methods Sex-specific associations between common European mitochondrial DNA haplogroups (H, U, J, T, K, V, W, I and X) and trajectories of cardiometabolic risk factors from birth to 18 years were examined in a prospective cohort. Cardiometabolic risk factors measured from birth/mid-childhood to 18 years included body mass index (BMI), fat and lean mass, systolic and diastolic blood pressure, pulse rate, high-density lipoprotein cholesterol (HDL-c), non-HDL-c and triglycerides. Fractional polynomial and linear spline multilevel models explored the sex-specific association between haplogroups and risk factor trajectories. Results Among a total of 7,954 participants with 79,178 repeated measures per outcome, we found no evidence that haplogroups U, T, J, K and W were associated with cardiometabolic risk factors compared to haplogroup H. In females, haplogroup V was associated with 4.0% (99% CI: -7.5, -0.6) lower BMI at age one but associations did not persist at age 18. Haplogroup X was associated with 1.3kg (99% CI: -2.5, -0.2) lower lean mass at age 9 which persisted at 18. Haplogroup V and X were associated with 9.3% (99% CI: -0.4, 19.0) and 16.4% (99% CI: -0.5,33.3) lower fat mass at age 9, respectively, although confidence intervals spanned the null and associations did not persist at 18. In males, haplogroup I was associated with 2.4% (99% CI: -0.5, 5.3) higher BMI at age 7; widening to 5.1% (99% CI: -0.5, 10.6) at 18 with confidence intervals spanning the null. Conclusions Our study demonstrated little evidence of sex-specific associations between mitochondrial DNA haplogroups and cardiometabolic risk factors.